(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In the current article, a model of oil pipes with dimensions of 1 centimeter was cut for the purpose of coating them with a system consisting of composite aluminum-tungsten carbide and with different reinforcing values of carbide (5,10,15,20,25) % and after performing the coating process by the method of thermal spraying with flame. Samples were heat treated at 1000°C for a time of only 2 hours. Then the test of hardness, porosity, adhesion strength and scanning electron microscope were conducted, and the results showed that the highest hardness was 222Hv, and the highest adhesive strength was 46 MPa, while the lowest porosity was 7%, while the electron microscope gave clear images of the coated samples in which the amount of consistency appeared crystal and mechanical interlocking